The Impact of a Dedicated Robotic Team on Robotic-Assisted Sacrocolpopexy Outcomes. Issue 4 (April 2018) - Carter-Brooks, Charelle M.; Du, Angela L.; Bonidie, Michael J.; Shepherd, Jonathan P.
Abstract : (Abstracted from Female Pelvic Med Reconstr Surg 2018;24:13–16) The use of robotic surgery in female reconstructive surgery has enabled more surgeons to perform sacrocolpopexies using a minimally invasive procedure. Compared with abdominal sacrocolpopexy, this approach is associated with decreased blood loss, postoperative pain, length of admission, and postoperative morbidity, but with similar long-term outcomes. The robotic-assisted surgical system is the most expensive modality for sacrocolpopexy and has been criticized for its high cost.